Speak Out. Intermediate. Workbook with key. 2nd Edition. - Clare, A., Wilson, JJ., Dimond-Bayir, S. (Harlow Pearson Education Limited, 2015)
Speakout 2nd Edition is a comprehensive six-level general English course for adults that has been developed in association with BBC Worldwide and Learning English. The course integrates authentic video from popular BBC programmes into every unit and builds the skills and knowledge learnens need to express themselves confidently in a real English-speaking environment.
Keywords: English Practice